TIPOLOGI, MOTIVASI DAN KARAKTERISTIK PERILAKU KOMUNITAS PECINTA ALAM WANADARI DALAM MELAKUKAN AKTIVITAS WISATA ALAM - Rifki Rahmanda Putra; Ute Lies Siti Khadijah; Cecep Ucu Rakhman; Awaludin Nugraha (Jurnal Pariwisata Pesona, 2020)
The aim of this study is to identify the motives behind the natural tourism activity made by Community of Nature Lovers Wanadri. The output of this study can be a reference for stakeholders or managers of a natural tourist attraction to do segmentation taking into account the preferences of archipelagic tourists based on the community and the development of natural tourism trends. This research is a quantitative approach. Primary data was collected through surveys and questionnaires to 88 respondents who were active members of the Wanadri Nature Lovers Community who were distributed through groups on one of the community's social media. The collected data is then processed using frequency analysis techniques. The results of the study showed that the Nature Lovers Community of Wanadri had novelty/learning motivation in conducting natural tourism trips, where they enjoyed learning new things in the natural attractions they visited. And then they had a preference for the types of tourism activities visiting historic/cultural activities namely studying sites or relics in a natural tourist attraction both in terms of history or culture. Based on their typology they belong to the type of hard core nature tourist where they carry out natural tourism activities by positioning themselves as observers of the environment and nature preservation